NAMPT as a Dedifferentiation-Inducer Gene: NAD+ as Core Axis for Glioma Cancer Stem-Like Cells Maintenance - Lucena-Cacace, Antonio; Umeda, Masayuki; Navas, Lola E.; Carnero, Amancio (Frontiers in Oncology, 2019)
Glioma Cancer Stem-Like Cells (GSCs) are a small subset of CD133+ cells with self-renewal properties and capable to initiate new tumors contributing to Glioma progression, maintenance, hierarchy and complexity. GSCs are highly resistant to chemo and radiotherapy. These cells are believed to be responsible for tumor relapses and patients’ fatal outcome after developing a recurrent Glioblastoma (GBM) or High Grade Glioma (HGG). GSCs are cells under replicative stress with high demands on NAD+ supply to repair DNA, maintain self-renewal capacity and to induce tumor plasticity. NAD+ feeds Poly-ADP polymerases (PARP) and NAD+-dependent deacetylases (SIRTUINS) contributing to GSC phenotype. This energetic core axis is mainly controlled by the rate-limiting enzyme nicotinamide phosphoribosyltransferase (NAMPT), an important oncogene contributing to tumor dedifferentiation. Targeting GSCs depicts a new frontier in Glioma therapy; hence NAMPT could represent a key regulator for GSCs maintenance. Its inhibition may attenuate GSCs properties by decreasing NAD+ supply, consequently contributing a better outcome together with current therapies for Glioma control.